INDONESIA-GERMANY-KENYA SOUTH-SOUTH TRIANGULAR COOPERATION IN ENERGY TRANSITION AS GLOBAL SOUTH SOLIDARITY - Wijanarka, Tunjung (KRITIS, 2025)
ABSTRACT This study examines Indonesia’s involvement in leveraging the South-South Triangular Cooperation (SSTC) as innovative development governance to promote the clean and renewable energy (EBT) transition in Indonesia, with a focus on partnership in the use of geothermal energy. Partnership within the SSTC framework includes governmental actors, including Indonesia, Germany, and Kenya, as well as coordination with non-state actors. The issue of development inclusivity is frequently a major impediment to achieving equal development in all sectors. Although the notion of Sustainable Development Goals (SDGs) has emerged as one of the driving factors of sustainable development, many barriers, such as funding issues and knowledge and technological limits, frequently highlight the inequality in growth in Global South countries. This study employs a qualitative research method with a descriptive analysis designation, as well as a literature study data-gathering approach to gather primary and secondary data. The author conducts the analysis study using postcolonial international relations theory as one perspective that can explain the underlying challenges of global development in Global South countries. Furthermore, the author employs the SSTC concept as an alternative form of development oriented toward Global South solidarity in order to achieve more inclusive development, such as the Indonesia-Germany-Kenya trilateral cooperation in realizing a clean and renewable energy transition, with a primary focus on Indonesia.